Adhesion reduction after knee surgery in a rat model by Mitomycin C - (:unkn) unknown (SPRINGER, 2011)
The purpose of this study was to investigate the effect of Mitomycin C on reduction in intra-articular fibrotic adhesion formation after knee surgery. Twenty female Wistar Albino rats were divided into two equal study groups. After skin incision, the right knees of animals were opened through a medial parapatellar approach, and the medial and lateral sides of the femoral condyle were exposed. A partial capsulotomy and synovectomy were performed. In group I, Mitomycin C was applied in the articular cavity of rats after hemostasis. An identical volume of sterile normal saline was applied in group II, which served as controls. All rats received weekly (6 weeks) intra-articular both Mitomycin C and saline starting from the day of operation. Animals were killed at 45 days after surgery. The presence and severity of osteo-capsular adhesion was assessed with both macroscopic and microscopic adhesion scoring systems. Results of macroscopic observations showed a significant reduction in both incidence and severity of adhesions in group I compared to group II. Histologically, adhesions in group I were thinner with less collagenic fibers. Microscopic determination of adhesion formation was less in group I, and the difference between groups was statistically significant. Our results suggest that post-operative administration of Mitomycin C may be considered a promising preventive therapy for the reduction in fibro-adhesive scars and consequent stiffness after knee surgery.
Keywords: Knee surgery; Adhesion formation; Mitomycin C; Prevention; PERITENDINOUS ADHESIONS; RABBIT MODEL; PREVENTION; BARRIER; GEL